OVARIAN HAEMODYNAMICS AND FERTILITY IN CATTLE - SATHESHKUMAR, S; RAJA, S (The Indian Journal of Animal Reproduction, 2022)
Ovarian vasculature is an important supportive component that ensures the fertility of an animal. Angiogenesisinvolves the formation of capillaries from pre-existing microvessels and therefore contributes to vascular remodellingand maturation. This process allows adequate nutritional and hormonal supply for ovarian follicle growth and corpusluteum (CL) formation. Colour-Doppler ultrasound has been used for studying vascular perfusion of ovarian structuresand to analyse the blood flow parameters through Doppler spectrum. The ovarian follicle and CL are the major sitesof active angiogenesis suggesting that a strong association between normal functionality of these structures and thenetwork of blood vessels. Rapid pulse frequency of the peri-follicular blood flow is a prerequisite factor for induction ofovulation process. Sequential observation during an oestrous cycle revealed progressive increase in luteal blood flowwith the increasing endocrine activity. There was an intense increase in luteal blood flow between days 15 – 17 of theoestrous cycle coinciding with the luteolysis. A deficient blood supply to the ovaries could disturb the folliculardevelopment, maturation and ovulation leading to various pathological conditions like anoestrus and cystic ovariandegeneration. More clinical research trials are required to develop suitable therapeutic protocols to modulate ovarianvascularity in order to enhance the fertility of cattle.
Keywords: Ovarian vascularity; angiogenesis; follicle; corpus luteum; fertility